1995
DOI: 10.1128/aac.39.8.1797
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of ceftazidime administered as continuous infusion or intermittent bolus alone and in combination with single daily-dose amikacin against Pseudomonas aeruginosa in an in vitro infection model

Abstract: We compared the pharmacodynamics and killing activity of ceftazidime, administered by continuous infusion and intermittent bolus, against Pseudomonas aeruginosa ATCC 27853 and ceftazidime-resistant P. aeruginosa 27853CR with and without a single daily dose of amikacin in an in vitro infection model over a 48-h period. Resistance to ceftazidime was selected for by serial passage of P. aeruginosa onto agar containing increasing concentrations of ceftazidime. Human pharmacokinetics and dosages were simulated as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 19 publications
8
38
0
1
Order By: Relevance
“…Although not statistically significant, we observed a greater reduction in bacterial density as a function of dosing interval. This relationship has been previously shown with cefepime against gram-negative organisms (6,9,11,12,41). The observed activity of cefepime against MRSA in this study may be related to some minimal activity against penicillin-binding protein 2a and/or due to a heteroresistance profile for beta-lactams in which some initial activity may be expected against a portion of the bacterial inoculum (40).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although not statistically significant, we observed a greater reduction in bacterial density as a function of dosing interval. This relationship has been previously shown with cefepime against gram-negative organisms (6,9,11,12,41). The observed activity of cefepime against MRSA in this study may be related to some minimal activity against penicillin-binding protein 2a and/or due to a heteroresistance profile for beta-lactams in which some initial activity may be expected against a portion of the bacterial inoculum (40).…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the most potent activity against MRSA was observed when cefepime was combined with an aminoglycoside. ␤-Lactams plus aminoglycoside have traditionally demonstrated synergy and additivity for a variety of pathogens, including P. aeruginosa, Enterobacteriaceae, and Acinetobacter (12,29,30,33,43,46). We found that combinations of cefepime plus an aminoglycoside administered every 12 h or every 24 h demonstrated the most potent activity.…”
mentioning
confidence: 81%
“…As noted, we did not observe changes in MICs. We and others previously have observed this regrowth phenomenon (7,22). Regrowth in the in vitro infection models appears to occur most often for antibiotics with time-dependent activity during pharmacokinetic simulations, where concentrations either stay just above the MIC or fall below the MIC during the course of dosing intervals.…”
Section: Discussionmentioning
confidence: 70%
“…The oxazolidinone is a timedependent antibiotic and for these drugs, the time above the MIC (T>MIC) is usually considered a critical parameter in the assessment of therapeutic efficacy (Carbon, 1990). In general, the maximal activity of continuous infusion was obtained at a steady-state concentration in serum equal to a multiple of the MIC, as previously demonstrated for ceftazidime (Cappelletty et al, 1995). To confirm this, continuous infusion of linezolid was used by Jacqueline et al to investigate whether it improves in vivo activity.…”
Section: In Vitro Antibacterial Activity Of Linezolid Alone and In Comentioning
confidence: 83%